(untitled) (Research, Society and Development, 2020)
Objective: to identify coping strategies, preventive measures and control of violence at work by health professionals in Primary Health Care. Method: this is a qualitative exploratory-descriptive study carried out in health units in the capital of Rio Grande do Sul , with 20 service professionals. Data collection took place between January and March 2020, through an audio-recorded press conference, transcribed and submitted to thematic content analysis. Results: professionals recognized their high exposure to violence at work, using strategies such as detachment, denial and flight to avoid the problem or equally aggressive reactions. The control measures identified were security support, support from colleagues and increased dialogue. Furthermore, they lack management support to prevent violence by improving infrastructure, access and social investments. Conclusion: the accomplishment of increments in the relationships and in the microspace are important, but managerial and social investments are fundamental.